High Detectivity All‐Printed Organic Photodiodes. (23rd September 2015) - Pierre, Adrien; Deckman, Igal; Lechêne, Pierre Balthazar; Arias, Ana Claudia
Abstract : All‐printed organic photodiode arrays on plastic are reported with average specific detectivities of 3.45 × 10 13 cm Hz 0.5 W −1 at a bias of −5 V. The blade‐coated polyethylenimine cathode interlayer and active layer, and screen‐printed anode enable precise device performance tunability and excellent homogeneity at centimetric scales. These devices' high operational reverse bias, good linear dynamic range, and bias stress stability make them attractive for implementation in imaging systems.